Activation of PERK/eIF2α/ATF4/CHOP branch of endoplasmic reticulum stress response and cooperation between HIF-1α and ATF4 promotes Daprodustat-induced vascular calcification - Tóth, Andrea; Lente, Gréta; Csiki, Dávid Máté; Balogh, Enikő; Szöőr, Árpád; Nagy, Béla; Jeney, Viktória (Frontiers in Pharmacology, 2024)
Introduction: Vascular calcification is accelerated in patients with chronic kidney disease (CKD) and increases the risk of cardiovascular events. CKD is frequently associated with anemia. Daprodustat (DPD) is a prolyl hydroxylase inhibitor for the treatment of CKD-associated anemia that enhances erythropoiesis through the activation of the hypoxia-inducible factor 1 (HIF-1) pathway. Studies showed that DPD promotes osteogenic differentiation of human aortic smooth muscle cells (HAoSMCs) and increases aorta calcification in mice with CKD. HIF-1 activation has been linked with endoplasmic reticulum (ER) stress; therefore, here we investigated the potential contribution of ER stress, particularly activating transcription factor 4 (ATF4), to the pro-calcification effect of DPD. Methods: Here, we used an adenine-induced CKD mouse model and HAoSMCs as an in vitro vascular calcification model to study the effect of DPD. Results: DPD treatment (15 mg/kg/day) corrects anemia but increases the expression of hypoxia (Glut1, VEGFA), ER stress (ATF4, CHOP, GRP78), and osteo-/chondrogenic (Runx2, Sox9, BMP2, Msx2) markers and accelerates aorta and kidney calcification in CKD mice. DPD activates the PERK/eIF2α/ATF4/CHOP pathway and promotes high phosphate-induced osteo-/chondrogenic differentiation of HAoSMCs. Inhibition of ER stress with 4-PBA or silencing of ATF4 attenuates HAoSMC calcification. DPD-induced ATF4 expression is abolished in the absence of HIF-1α; however, knockdown of ATF4 does not affect HIF-1α expression. Conclusion: We concluded that DPD induces ER stress in vitro and in vivo, in which ATF4 serves as a downstream effector of HIF-1 activation. Targeting ATF4 could be a potential therapeutic approach to attenuate the pro-calcific effect of DPD.